2018
DOI: 10.1111/jiec.12779
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Visualization and Industrial Ecology: Applications, Challenges, and Opportunities

Abstract: Summary The emergence of increasingly complex data in industrial ecology (IE) has caused scholarly interest in interactive visualization (IV). IV allows users to interact with data, aiding in processing and interpreting complex datasets, processes, and simulations. Consequently, IV can help IE practitioners communicate the complexities of their methods and results, shed light on the underlying research assumptions, and enable more transparent monitoring of data quality and error. This can significantly increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…As the usability of the platform increases, the efficiency of the user’s decision-making process intensifies and user satisfaction increases. Such visualization of results is regarded in all types of information systems facilitating IS ( Font Vivanco et al , 2019 ; Lütje et al , 2018 ; van Capelleveen et al , 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the usability of the platform increases, the efficiency of the user’s decision-making process intensifies and user satisfaction increases. Such visualization of results is regarded in all types of information systems facilitating IS ( Font Vivanco et al , 2019 ; Lütje et al , 2018 ; van Capelleveen et al , 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another data visualization approach proposed to simplify the interpretation of the results is through Sankey Diagrams. Additionally, heat maps are used with the aid of geo-spatial related data and energy related process data ( Font Vivanco et al , 2019 ; Holgado et al , 2018 ; Hsien et al , 2020 ; Lütje et al , 2018 ; Lütje et al , 2019 ; van Capelleveen et al , 2021 ; Yeo et al , 2019b )…”
Section: Resultsmentioning
confidence: 99%
“…To make data inputs more valid or their validity at least testable, scholars have been promoting data transparency (Hertwich et al., 2018). Recent examples of similar efforts include proposals for interactive visualization of data (Font Vivanco et al., 2019); general, method‐independent data model (Pauliuk, Heeren, Hasan, & Müller, 2019); investigation of uncertainty quantification and distribution in LCA (Ross & Cheah, 2019; Weidema, 2018); estimation of uncertainty (Min & Rao, 2018) and aggregation bias (Zhang, Caron, & Winchester, 2019) in using multiregional IO tables; and quantitative evaluation of MFA data quality and uncertainty (Schwab & Rechberger, 2018; Schwab, Laner, & Rechberger, 2017). Along this line, the Journal of Industrial Ecology ( JIE ) has developed data openness badges to acknowledge authors’ efforts in making data transparent and accessible.…”
Section: Toward More Transparent and Reliable Evidence: Advances In Data And Methodsmentioning
confidence: 99%
“…So far, SEM studies have addressed the aspects above by using different approaches and tools. For example, interactive visualizations and simulators have been used to improve the communication and interpretation of the results of studies representing complex systems (Riehmann et al., 2005; Vivanco et al., 2018). However, it has been found that learning through interactive visualizations and simulators mainly occurs in guided aftermath discussions (Dieleman & Huisingh, 2006; Milrad et al., 2003).…”
Section: Outreach Of Sem Studiesmentioning
confidence: 99%